2020
DOI: 10.1186/s12895-020-00102-1
|View full text |Cite
|
Sign up to set email alerts
|

The ceramide [NP]/[NS] ratio in the stratum corneum is a potential marker for skin properties and epidermal differentiation

Abstract: Background: Specific species of ceramides (Cer), major constituents of lipids in the stratum corneum (SC), are decreased and are correlated with SC barrier and water-holding functions in the skin of patients with atopic dermatitis (AD) or psoriasis (Pso). However, possible correlations between Cer subclass ratios and skin properties in barrier-disrupted skin and in healthy skin remain unclear. The objective of this study was to identify a new marker to evaluate skin properties and epidermal differentiation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…Bouwstra et al also clarified that such changes in SC ceramides were more markedly observed in the skin lesions than in the normal skin of AD patients [ 63 , 64 , 65 ]. Other studies have confirmed that similar changes in SC ceramides occur in AD [ 66 , 67 , 68 ].…”
Section: Altered Amount and Composition Of Ceramides And Other Lipids In The Skin Of Patients With Adsupporting
confidence: 59%
See 1 more Smart Citation
“…Bouwstra et al also clarified that such changes in SC ceramides were more markedly observed in the skin lesions than in the normal skin of AD patients [ 63 , 64 , 65 ]. Other studies have confirmed that similar changes in SC ceramides occur in AD [ 66 , 67 , 68 ].…”
Section: Altered Amount and Composition Of Ceramides And Other Lipids In The Skin Of Patients With Adsupporting
confidence: 59%
“…As noted above, AD skin is associated with lipid abnormalities ( Figure 5 ). Collectively, the extractable SC lipids, such as acylCer, Cer[NP], and Cer[NH], are reduced, whereas Cer[AS] and Cer[NS] are increased [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. In addition, short-chain rather than long-chain ceramides are increased [ 62 , 63 , 64 , 65 ].…”
Section: Altered Amount and Composition Of Ceramides And Other Lipids In The Skin Of Patients With Admentioning
confidence: 99%
“…The most common lipid in the stratum corneum, ceramide, has multiple subtypes. The prevalence of ceramide subtypes differ in psoriatic lesions, in a manner which is correlated with transepidermal water loss [ 51 ]. The total amount of ceramide in keratinocytes and fibroblasts is not reduced in psoriatic lesions, suggesting that this effect is from the dysregulation of the ceramide subtype, rather than a reduction of the lipid [ 52 ].…”
Section: Barrier Aberration In Psoriasismentioning
confidence: 99%
“…The structure of the epidermis is schematically represented in Figure 1. The outermost sublayer of the epidermis, named stratum corneum (SC) (10-20 µm), plays a fundamental role as the body's first and main physical skin barrier from external menaces [19][20][21]. It consists of corneocytes-specific cells that are the essential limiting factor for permeation through the skin, restricting the passage of molecules significantly larger than 500 Da [22].…”
Section: Skinmentioning
confidence: 99%